COVID-19 and the adoption of E-Business among Sarawak's Women Entrepreneurs / Nadrawina Isnin ... [et al.] - Isnin, Nadrawina; Juman, Debbra; Ishak, Nur Anisha Khuzaimah; Mahmud, Noorfadhleen (2021)
Over 4.3 million confirmed cases and 290,000 deaths have been reported worldwide because of the COVID-19 pandemic. It has also generated concerns about an approaching economic downturn. Social isolation, self-isolation, and travel limitations have resulted in a reduction in the workforce across all economic sectors, resulting in the loss of much employment (Nicola et al., 2020). To that, World Health Organization (WHO, 2021) announced that COVID-19 became a pandemic on March 11, 2020, with a 13-fold increase in the number of cases outside of China and a tripling of the number of countries afflicted. As a result, there are over 118,000 cases in 114 countries, with 4,291 people dying as a result. Thus, WHO expected the number of cases, deaths, and affected countries to continue to rise in the next days and weeks. Governments have implemented border closures, travel restrictions (Jazeera, 2020 & GOV.UK, 2020), and quarantine in countries that make up the world's top economy to 'flatten the curve,' (Avi, 2020) raising fears of an approaching economic crisis and recession (Buck et al., 2020).